Novel selective PDE type 1 inhibitors cause vasodilatation and lower blood pressure in rats. (5th July 2017) - Laursen, Morten; Beck, Lilliana; Kehler, Jan; Christoffersen, Claus Tornby; Bundgaard, Christoffer; Mogensen, Susie; Mow, Tomas Joachim; Pinilla, Estéfano; Knudsen, Jakob Schöllhammer; Hedegaard, Elise Røge; Grunnet, Morten; Simonsen, Ulf
Abstract : Background and Purpose: The PDE enzymes (PDE1–11) hydrolyse and thus inactivate cyclic nucleotides and are important in the regulation of the cardiovascular system. Here, we have investigated the effects on the cardiovascular system, of two novel selective PDE1 inhibitors, Lu AF41228 and Lu AF58027. Experimental Approach: We used rat mesenteric small arteries (internal diameters of 200–300 μm), RT‐PCR and measured isometric wall tension. Effects of Lu AF41228 and Lu AF58027 on heart rate and BP were assessed in both anaesthetized and conscious male rats. Key Results: Nanomolar concentrations of Lu AF41228 and Lu AF58027 inhibited PDE1A, PDE1B and PDE1C enzyme activity, while micromolar concentrations were required to observe inhibitory effects at other PDEs. RT‐PCR revealed expression of PDE1A, PDE1B and PDE1C in rat brain, heart and aorta, but only PDE1A and PDE1B in mesenteric arteries. In rat isolated mesenteric arteries contracted with phenylephrine or U46619, Lu AF41228 and Lu AF58027 induced concentration‐dependent relaxations which were markedly reduced by inhibitors of guanylate cyclase, ODQ, and adenylate cyclase, SQ22536, and in preparations without endothelium. In anaesthetized rats, Lu AF41228 and Lu AF58027 dose‐dependently lowered mean BP and increased heart rate. In conscious rats with telemetric pressure transducers, repeated dosing with Lu AF41228 lowered mean arterial BP 10–15 mmHg and increased heart rate. Conclusions and Implications: These novel PDE1 inhibitors induce vasodilation and lower BP, suggesting a potential use of these vasodilators in the treatment of hypertension and vasospasm.